(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
An assessment of the quality of basic pharmacotherapy in patients with ischemic stroke and an analysis of the frequency and nature of cardiovascular complications according to prospective follow-up data was carried out. The study included 114 patients with acute ischemic stroke and sinus rhythm. After discharge from the hospital, a telephone survey was used to assess patients’ adherence to medication and the frequency of cardiovascular complications was recorded. The prospective follow-up period was 21 months (15 months; 44 months). Cardiovascular complications were observed in 33 patients (21%), of which 11 (8%) were fatal. These 11 patients were older than the rest, had a greater number of repeated ischemic strokes, more stable forms of coronary heart disease (post-infarction cardiosclerosis, angina pectoris), a higher risk of cardiovascular complications on the ESRS scale and a smaller amount of treatment with diuretics, antithrombotic drugs, especially indirect anticoagulants (p<0.05).